The Implications of Trade Barriers for Sectoral Diversification and Macroeconomic Stability in Developing Economies - Srour, Gabriel (Washington, D.C. : International Monetary Fund, 2006)
The paper examines the implications of lower trade barriers for sectoral diversification and macroeconomic stability in developing economies with a large primary goods sector. It shows that lower trade barriers can have ambiguous effects on macroeconomic stability. It shows also that diversification, in the form of equal distribution of resources between nonprimary sectors, may be counterproductive. In fact, investment in the nonprimary sector with lower trade barriers unambiguously enhances macroeconomic stability in a developing economy that is subject to substantial primary shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet